Neurotoxic Methamphetamine Doses Increase LINE-1 Expression in the Neurogenic Zones of the Adult Rat Brain - Moszczynska, Anna (Sci Rep, 2015)
Methamphetamine (METH) is a widely abused psychostimulant with the potential to cause neurotoxicity in the striatum and hippocampus. Several epigenetic changes have been described after administration of METH; however, there are no data regarding the effects of METH on the activity of transposable elements in the adult brain. The present study demonstrates that systemic administration of neurotoxic METH doses increases the activity of Long INterspersed Element (LINE-1) in two neurogenic niches in the adult rat brain in a promoter hypomethylation-independent manner. Our study also demonstrates that neurotoxic METH triggers persistent decreases in LINE-1 expression and increases the LINE-1 levels within genomic DNA in the striatum and dentate gyrus of the hippocampus, and that METH triggers LINE-1 retrotransposition in vitro. We also present indirect evidence for the involvement of glutamate (GLU) in LINE-1 activation. The results suggest that LINE-1 activation might occur in neurogenic areas in human METH users and might contribute to METH abuse-induced hippocampus-dependent memory deficits and impaired performance on several cognitive tasks mediated by the striatum.